Molecular prevalence and diversity of zoonotic bacteria of invasive Rattus from South Africa, with emphasis on the genera Rickettsia and Streptobacillus - Bastos, Armanda D.S. (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2013.